A test of the matched filter hypothesis in two sympatric frogs, Chiromantis doriae and Feihyla vittata. Issue 5 (3rd September 2019) - Yang, Yue; Zhu, Bicheng; Wang, Jichao; Brauth, Steven E.; Tang, Yezhong; Cui, Jianguo
ABSTRACT: The matched filter hypothesis proposes that the auditory sensitivity of receivers should match the spectral energy distribution of the senders' signals. If so, receivers should be able to distinguish between species-specific and hetero-specific signals. We tested the matched filter hypothesis in two sympatric species, Chiromantis doriae and Feihyla vittata, whose calls exhibit similar frequency characters and that overlap in the breeding season and microenvironment. For both species, we recorded male calls and measured the auditory sensitivity of both sexes using the auditory brainstem response (ABR). We compared the auditory sensitivity with the spectral energy distribution of the calls of each species and found that (1) auditory sensitivity matched the signal spectrogram in C. doriae and F. vittata ; (2) the concordance conformed better to the conspecific signal versus the hetero-specific signal. In addition, our results show that species differences are larger than sex differences for ABR audiograms.